1
$\begingroup$

I'm studying Lie bialgebras: https://en.wikipedia.org/wiki/Lie_bialgebra.

I'm a bit confused about the way of writing the so called "dual Jacobi identity".

On Majid's book "a Quantum group Primer" it is written as $$\tag{1} (\delta \otimes 1 )\circ \delta (X_i) + cyclic =0,\,\,\,\,\,X_i \in g $$where $\delta:g \to g\otimes g $ is the skew symmetric co-commutator map, $g$ a Lie algebra.

My question is very simple: what is "$+cyclic$" in (1)? I understand the basis dependent identity but I'm unable to write down the other 2 bits in the basis independent version.. I guess one is simply: $(1 \otimes \delta )\circ \delta (X_i)$ but what can one rotate next? (1) needs to be applied to a single Lie algebra element $X$..

Thank you!

$\endgroup$
0
$\begingroup$

another way to write co-acobi equaton is the following: Consider $g$ as vector space ad $\Lambda g$ (the exterior algebra on $g$) as algebra. From a linear map $\delta:g\to g\wedge g$, you can extend it as a degree 1 derivation (notice $\Lambda g$ is super commutative and free as such, so any super-derivation is determined by its values on $g$. Also, since the degree is given by the tensor degree, $\delta:g\to\Lambda^2g$ is a degree 1 linear map). So, what is the meaning of extending by superderivation? write using Sweedler-type notation $$ \delta x = x_1\wedge x_2 $$ then, the extended derivation (let us call $\delta$ again) is given by (for $a,b\in g$) $$ \delta(a\wedge b)=\delta( a)\wedge b - a\wedge \delta b\in\Lambda^3 g $$ Notice also (always $a,b\in g$) $$ \delta( a)\wedge b - a\wedge \delta( b) =\delta( a)\wedge b - \delta( b)\wedge a $$ so, you can write the above formula in terms of $\delta\otimes 1$ and anti-symmetrization maps.

The full anti-symmetrization map (from $g^{\otimes 3}$ to $\Lambda^3 g$) has 6 terms, but if you already know some partial antisymmetry (e.g. $\sum "a\otimes b"=\delta x\in\Lambda^2 g$ is antisymmetric) then the six terms are actually three terms twice.

The same happens if you write Jacoby identity as $$ \sum_{\sigma\in S_3}(-1)^\sigma[[x_{\sigma(1)},x_{\sigma(2)}],x_{\sigma(3)}] =2([[x_1,x_2],x_3]+[[x_2,x_3],x_1]+[[x_3,x_1]x_2]) $$ just because $[x_i,x_j]=-[x_j,x_i]$.

As a final remark, instead of using the description of Majid's book, I prefer the definition "co-Jacoby is the condition $\delta^2=0$, where $\delta$ is the unique super-derivation on $\Lambda g$ with restriction to $g$ equal to the cobracket."

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.